Efecto del impuesto predial en el presupuesto institucional de la Municipalidad del Centro Poblado de Salcedo, Puno – Perú, 2020 - Quispe Mamani, Julio Cesar (2021)
The objective of this research was to determine the level of influence of the property tax on the institutional budget of the Municipality of the Centro Poblado de Salcedo, for which the descriptive, explanatory and correlational methodology was applied; considering the use of the econometric model of ordinary least squares and multinomial logit. It was determined that the collection of property tax directly influenced the institutional budget, in addition, the influence was direct (Positive) of the improvement of municipal services in the level of property tax payments by citizens and the improvement of services municipalities directly influenced citizen satisfaction.